Pengaruh Evaluasi Kinerja dan Motivasi Kerja terhadap Kualitas Layanan RSUD dr. Soeratno Gemolong Sragen - Kismanto, Joko; Pujilestari, Agustina; Rahardjoputro, Rolando; Muyasaroh, Airin; Margareta, Salsa Maria (Valid: Jurnal Ilmiah, 2024)
Service quality is the main basis for knowing the level of consumer satisfaction, in which case a company can be said to be good if it is able to provide goods or services in accordance with customer desires. The aim of the research is to determine performance evaluation and work motivation on service quality at RSUD dr. Soeratno Gemolong Sragen. This type of research is descriptive correlational, namely research that aims to find relationships between variables. Cross-sectional research approach. How to take simple random sampling with a sample of employees at RSUD dr. Soeratno Gemolong Sragen. The method of collecting data is using a questionnaire, where hypothesis testing uses descriptive statistical analysis with F test analysis, t test. The results of this research show that variables, performance evaluation, and work motivation have a positive and significant influence partially or simultaneously on service quality variables. The results of this research also show that the dominant variable that has an influence on service quality is the work motivation variable.